2014
DOI: 10.1016/j.jval.2014.03.068
|View full text |Cite
|
Sign up to set email alerts
|

4 Your Kids Care: Reducing Non-Emergent Hospitalization In A Medicaid Pediatric Population Through Hands-On Training And Parent/Caregiver Education

Abstract: objeCtives: In 2012 United States Food and Drug Administration (FDA) created a new expedited pathway of 'Breakthrough Therapy Designation' (BTD) to enable early approval of therapies, which have shown substantial activity in early trials. The objective of this study was to understand the impact on BTD on patients and payers. Methods: The data for number of granted BTDs was obtained from FDA. gov. The data for publically disclosed BTDs was obtained from sponsor's press releases. For all products the information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…There was no statistically significant difference in the urgency of presentations or admissions pre/post‐COVID‐19. This contrasts with previous studies, which found decreased presentation rates, decreased NUPs and increased admission rates 17,18,20,21 . It would be worthwhile to see whether there is any change in presentations/admission post‐Delta variant where the caseloads were much higher than had been seen the year prior.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…There was no statistically significant difference in the urgency of presentations or admissions pre/post‐COVID‐19. This contrasts with previous studies, which found decreased presentation rates, decreased NUPs and increased admission rates 17,18,20,21 . It would be worthwhile to see whether there is any change in presentations/admission post‐Delta variant where the caseloads were much higher than had been seen the year prior.…”
Section: Discussioncontrasting
confidence: 62%
“…19 Similarly, a study by Grant et al examining the effect of a short programme that aimed at providing education on how to deal with common childhood illnesses to parents and advising for review by primary care provider before seeking ED care showed a decrease in NUPs among the study group who received an education. 20 This study also found that neonates with younger mothers were more likely to have NUPs to the ED. This finding is consistent with previous studies identifying younger maternal age as a risk factor.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations